An introduction to biblical hermeneutics: the search for meaning - Kaiser, Walter C., Jr. (Zondervan, 2007)
The search for meaning : initial directions -- Understanding the text : meaning in literary genres -- Responding to the text : meaning and application -- The search for meaning : further challenges